Response of herbaceous wetland plant species to changing precipitation regimes. Issue 8 (31st August 2018) - Didiano, Teresa J.; Johnson, Marc T.J.; Duval, Tim P.
Abstract: The structure of wetland plant communities is sensitive to patterns of precipitation. In some regions, climate change is expected to result in more large‐magnitude, infrequent precipitation events. Typically, the response of wetland plants to changing precipitation regimes is studied under alterations in the amount of precipitation (drought), rather than event frequency. Here, we seek to understand how changes in rainfall frequency affect (a) soil moisture variability, (b) plant performance, and (c) plant C and N concentrations. We conducted a greenhouse study using eight herbaceous plant species (three eudicots, five monocots) subject to three precipitation treatments: (a) 80 mm per month distributed in equal volumes every 3 days (control treatment), (b) 80 mm per month distributed every 15 days (infrequent treatment), and (c) 110 mm per month distributed every 15 days (large magnitude‐infrequent treatment). Infrequent treatments decreased soil moisture by >60% compared with the control. Rainfall frequency affected soil moisture losses to evapotranspiration, which differed between early‐ and late‐growing seasons. This soil moisture stress in the infrequent treatments contributed to a 10–49% decrease in biomass among all eudicot species and a 25–54% decrease in two monocots. In contrast, changes in C and N concentration were limited to two forb species. Our results show that changes in precipitation frequency can strongly impact some wetland species. For some impacted species increased magnitude can alleviate the negative effects of infrequent rainfall. These results provide insight into how forecasted changes in the frequency and magnitude of precipitation may affect wetland plant species.